Novel transcriptome networks are associated with adaptation of capsicum fruit development to a light-blocking glasshouse film - He, Xin; Solis, Celymar A.; Chavan, Sachin G.; Maier, Chelsea; Wang, Yuanyuan; Liang, Weiguang; Klause, Norbert; Ghannoum, Oula; Cazzonelli, Christopher I.; Tissue, David T.; Chen, Zhong-Hua (Frontiers in Plant Science, 2023)
Light-blocking Films (LBFs) can contribute to significant energy savings for protected cropping via altering light transmitting, such as UVA, PAR, blue and red spectra affecting photosynthesis and capsicum yield. Here, we investigated the effects of LBF on orange color capsicum (O06614, Capsicum annuum L.) fruit transcriptome at 35 (mature green) and 65 (mature ripe) days after pollination (DAP) relative to untreated control in a high-tech glasshouse. The results of targeted metabolites showed that LBF significantly promotes the percentage of lutein but decreased the percentage of zeaxanthin and neoxanthin only at 35 DAP. While the 35 DAP fruits were less impacted by LBF treatment (versus control) with a total of 1,192 differentially expressed genes (DEGs) compared to 2,654 DEGs at 65 DAP. Response to stress and response to light stimulus in Biological Process (BP) of Gene Ontology (GO) were found in 65 DAP fruits under LBF vs Control, and clustering analysis revealed a predominant role of light receptors and phytohormone signaling transduction, starch and sucrose metabolism in LBF adaptation. The light signaling DEGs, UV light receptor UVR8, transcription factors phytochromes interacting factor 4 (PIF4), and an E3 ubiquitin ligase (COP1) were significantly downregulated at 65 DAP. Moreover, key DEGs in starch and sucrose metabolism (SUS, SUC, INV), carotenoid synthesis (PSY2, BCH1), ascorbic acid biosynthesis (VTC2, AAO, GME), ABA signaling (NCED3, ABA2, AO4, PYL2/4) and phenylpropanoid biosynthesis (PAL, DFR) are important for the adaptation of 65 DAP fruits to LBF. Our results provide new candidate genes for improving quality traits of low-light adaptation of capsicum in protected cropping.